The Warriors: A CSR model for ESL trainers / Razanawati Nordin ... [et al.] - Nordin, Razanawati; Saad, Sharina; Hasan, Asrol; Mansor, Nur Syazwanie; Abu Hassan, Nor Asni Syahriza; Amat, Rafidah (2022)
The Warriors - Life is a battle, Warrior Up! is a unique corporate social responsibility (CSR) training module for teaching languages to rural school students in Baling, Kedah. The language experts have designed a CSR module that consists of language games that can cater to the school children's learning styles - the kinesthetic style which consists of task-based activities located at several pit-stops focusing on the four language learning skills – reading, writing, speaking, and listening. This module requires students in groups to explore and make decisions to complete all tasks at each pit stop. This model is an adaptation of collaborative learning, game-based learning, and autonomous learning where various aspects of language learning strategies have been integrated to enhance language proficiency. Students are introduced to cognitive, mnemonic, metacognitive, affective, and social skills to improve their confidence in using languages for a day program. By the day's end, trainers observed that most students were excited as they had shown high participation, enjoyment, and engagement. The participants had dared to challenge themselves and be warriors to use the language courageously.